EXPERIMENTAL STUDY OF CHEMOTHERAPY RELATED LEUKOCYTOPENIA TREATED BY VARIOUS PEROAL LEUCOCYTE INCREASING DRUGS - Xiping, Zhang; Hongjian, Yang; Dehong, Zou; Xiangming, He; Xingfei, Yu; Yongfeng, Li (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Clinically, the patients with significant WBC decrease are mostly administered G-CSF, this kind of drugsis expensive and adverse reactions are often seen. In contrast, oral leucocyte increasing drug has small adversereactions, can be used for longer time and can improve the continuity and stability of treatment. The experimental studybased on study of mouse was to evaluate the effects of treatment and chemotherapy of related leukocytopenia by fivekinds of commonly used peroal leucocyte increasing drugs.Materials and Methods: We prepared mice chemotherapy related leukocytopenia model by cyclophosphamideintraperitoneal injection, the positive control drug is G-CSF, respectively fill five kinds of peroal Leucocyte increasingdrugs (Qijiao Shengbai Capsule, Weixuening Granule, Compound Zaofan Pill, Berbamine and Leucogen Tablets) in thestomach, the experimental group was divided into normal control group (group A), model group (group B), positivecontrol group (Group rhG-CSF, group C) and treatment groups (group D-H), and treatment groups were divided intoQijiao Shengbai Capsule group (group D), Weixuening Granule group (group E), Compound Zaofan Pill group (groupF), Berbamine Tablet group (group G) and Leucogen Tablet group (group H). Calculate the death rate, blood routineand important visceral organ index in each group..Results: The death rate of mice in each group has no significant difference (P>0.05). WBC of B, D, E and F groupswas significantly lower than that of group A (P<0.05 or P<0.01). WBC of C, G and H groups was significantly higherthan those of group B (P<0.01). WBC of D, E and F groups was significantly lower than that of group C (P<0.01).WBC of G and H groups was significantly higher than that of D and F groups (P<0.01), WBC of group H issignificantly higher than that of group E (P<0.05). RBC of group F, G and H groups was significantly higher than thatof group D (P<0.05 or P<0.01). HB of group H is significantly higher than that of group A (P<0.01). HB of C, G and Hgroups was significantly higher than that of group B (P average <0.01). HB of D, E and F groups was significantlylower than that of group C (P<0.05 or P<0.01). HB of G and H groups was significantly higher than that of D, E and Fgroups (P average <0.01). PLT of group H was significantly higher than that of group B (P average <0.05). PLT of F, Gand H groups was significantly higher than that of group D (P<0.01). Lung index of group G was significantly higherthan that of D, E, F and H groups (P<0.01). Liver index of group H is significantly higher than that of group D (P<0.05).Thymus index of G and H groups is significantly higher than that of group F (P<0.05 or P<0.01).Conclusions: Among all drugs of rising WBC, G-CSF owns strongest effect. In oral drug groups, WBC rising effect ofLeucogen Tablets is best, RBC, HB and PLT improvement effect of Berbamine and Leucogen Tablets is best. Inaddition, Berbamine and Leucogen Tablets respectively caused significant increase of lung and liver index, whatindicates that, the two drugs may be accompanied by relevant viscera damage. At the same time, the two drugs alsoincreased thymus index, which indirectly indicates that, the immunity and regulation abilities of Berbamine andLeucogen Tablets are stronger. The spleen index of Qijiao Shengbai Capsule group was significantly higher than that ofBerbamine Tablet and Leucogen Tablet groups, what indicates that, the immunity and regulation abilities of QijiaoShengbai Capsule may be stronger in oral drug group.